Surface modification of BiOBr/TiO2 by reduced AgBr for solar-driven PAHs degradation: Mechanism insight and application assessment - Xianbo Sun; Weiyu He; Hao, Xiaodi; Ji, Haodong; Liu, Wen; Cai, Zhengqing (Journal of Hazardous Materials, 2021)
A novel solar active AgBr/BiOBr/TiO2 catalyst was synthesized by a facile coprecipitation method for solar-driven water remediation. The synthesized material composed of flower-like TiO2 nanoparticles loaded on BiOBr nanosheets and with homogeneous surface distributed Ag/AgBr nanoparticles. The internal electric field between BiOBr/TiO2 heterojunction greatly facilitated the charge carrier migration; the introduction of narrow band gap semiconductors (AgBr and BiOBr) promoted the visible light adsorption; and the Ag/AgBr nanoparticles acted as photosensitizer to further improve the light utilization. The new material showed 7.6- and 4.0-times activity of pure TiO2 and BiOBr under solar light, and the contribution of reactive species on anthracene degradation followed the order of h+ >O2•−> •OH. The degradation mechanism and pathway were proposed based on intermediates analysis and DFT calculation. The QSAR analysis revealed that the environmental risks of contaminants were greatly reduced during the photocatalysis process but some intermediates were still toxic. The high photocatalytic activity, stability and adaptability all indicated that this new material owns great application potential for cost-effective photocatalytic remediation of persistent organic contaminants under solar light.
Keywords: BiOBr/TiO; pahs; Photocatalytic; Solar; Toxicity